Novel Scale‐Like Structures of Graphite/TiC/Ti3C2 Hybrids for Electromagnetic Absorption. (11th April 2018) - Li, Mian; Han, Meikang; Zhou, Jie; Deng, Qihuang; Zhou, Xiaobing; Xue, Jianmin; Du, Shiyu; Yin, Xiaowei; Huang, Qing
Abstract: Electromagnetic (EM) absorbing and shielding materials have attracted great interests due to the increasing electromagnetic pollutions in the past years. Microstructure plays a crucial role in determining the performance of the above materials. Herein, a scale‐like structure based on Ti3 C2 Mxenes is proposed to approach improved EM absorption properties. For the first time, graphite/TiC/Ti3 AlC2 (G/TiC/Ti3 AlC2 ) hybrids are fabricated in a molten salts bath and graphite/TiC/Ti3 C2 (G/TiC/Ti3 C2 ) hybrids are obtained after Al atoms are etched from G/TiC/Ti3 AlC2 . In G/TiC/Ti3 C2, Ti3 C2 sheets are perpendicular to the plane of G/TiC, which like a bionic structure of fish scale. The scale‐like G/TiC/Ti3 C2 hybrids are dispersed in paraffin matrix to evaluate the EM properties. Owing to the structure‐induced EM absorption mechanism, G/TiC/Ti3 C2 show much enhanced EM absorption ability than those materials without structure design, e.g., G/TiC/Ti3 AlC2, pure Ti3 C2, G/TiC, and the simple mixture of G/TiC with Ti3 C2 (G/TiC+Ti3 C2 ). The minimum reflection coefficient (RC) of G/TiC/Ti3 C2 with the sample thickness of 2.1 mm reaches −63 dB and the effective absorption bandwidth (the frequency where RC is lower than −10 dB) is more than 3.5 GHz. The results indicate that the scale‐like structure can greatly improve the EM absorption ability. Abstract : Graphite/TiC/Ti3 C2 hybrids with scale‐like structure is fabricated to approach improved electromagnetic absorption properties. The results indicate that the specific interfacial junction of graphite/TiC/Ti3 C2 can greatly improve the electromagnetic absorption ability. The minimum reflection coefficient of graphite/TiC/Ti3 C2 hybrids reaches −63 dB and the effective absorption bandwidth is more than 3.5 GHz.